Quantification of mast cells in different stages of periodontal disease - Marjanović, Dragan; Anđelković, Zlatibor; Brkić, Zlata; Videnović, Goran; Šehalić, Meliha; Matvijenko, Vladimir; Leštarević, Snežana; Đorđević, Nadica (Vojnosanitetski pregled, 2017)
Background/Aim. Mast cells are mononuclear cells originating from bone marrow. They produce various biologically active substances, which allow them to actively participate in immune and inflammatory processes associated with periodontal disease. The study focused on distribution and density of mast cells in healthy gingiva as well as in different stages of periodontal disease. Methods. The material used for this purpose was gingival biopsies taken from 96 patients classified into 4 groups: healthy gingiva, gingivitis, initial and severe periodontal disease. Toluidine blue staining according to Spicer was utilized for identifying mast cells. Results. Basing on our study, the density of mast cells in the gingival tissue increases with the progression of the infection, which means they are more numerous in gingivitis compared to healthy gingiva, as well as in periodontal disease compared to gingivitis. Conclusion. Increase in the number of mast cells in the infected gingiva can be correlated with an increased influx of inflammatory cells from blood circulation into the gingival stroma, as well as with the collagen lysis, since these cells produce substances with collagenolytic potential. Based on the distribution of mast cells, it could be concluded that in the evolution of periodontal disease there are significant dynamic alterations in migration and localization of these cells.